KONTRIBUSI PAJAK HOTEL DAN RESTORAN TERHADAP PENINGKATAN PENDAPATAN ASLI DAERAH KOTA SURABAYA - Candrasari, Anita; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Hotel and restaurant taxes are two types of local taxes which its potency is growing with the existence of supporting components from the service, development or even tourism sector in the enhancement of local development. The municipal government of Surabaya in the implementation of tax collection tries to implement the development which is potential to the target achievement and the better realization. This research is meant to find out the rates of potential achievement, effectiveness, and hotel and restaurant tax contribution to the local own source revenue of Surabaya city. The research analysis method has been done by using descriptive qualitative and the collection technique of the primary data is in the form of interview, observation, and documentation and the secondary data which contains the amount of local tax revenue and local own source revenue in order to analyze the rates of potential achievement, effectiveness, and tax contribution. The result of this research shows that the tax potency in 2010-2014 experiences enhancement in accordance with the government regulation in collecting their tax. The effectiveness rates of hotel tax is very effective in 2010-2014, the highest improvement of effectiveness in 2012 is 106.95%. The effectiveness of restaurant tax in 2012 is 108.21% shows very effective improvement has occurred. Even though, the realization of hotel and restaurants tax revenue and the realization of local own source revenue has increased but the contribution in 2010-2014 are decreased, the contribution of hotel and restaurant tax which has been achieved by the DPPK of Surabaya is quite significant in providing the enhancement of local revenues and the government has been trying to make improvement in collecting their tax.Keywords: Hotel and Restaurant Tax, Potential, Effectiveness, Contribution, Local Own Source Revenue.